Employee Mental Health During COVID-19 Adaptation: Observations of Occupational Safety and Health/Human Resource Professionals in Ireland - Chen, Yanbing; Ingram, Carolyn; Downey, Vicky; Roe, Mark; Drummond, Anne; Sripaiboonkij, Penpatra; Buckley, Claire; Alvarez, Elizabeth; Perrotta, Carla; Buggy, Conor (International journal of public health, 2022)
Objectives: This study aims to understand mental health issues among Irish employees arising from COVID-19 adaptation from the perspective of Occupational Safety and Health (OSH) and/or Human Resource (HR) professionals. Methods: Fifteen focus groups including 60 OSH/HR professionals from various sectors were conducted covering four predetermined themes. The data were transcribed verbatim, with transcripts entered into Nvivo for thematic analysis incorporating intercoder reliability testing. Results: The mental health impacts among employees are identified from three stages: pre-adaptation, during adaptation, and post-adaptation. Most issues were reported during the second stage when working conditions dramatically changed to follow emerging COVID-19 policies. The identified mental health support from participating organizations included providing timely and reliable information, Employee Assistance Programme (EAP), informal communication channels, hybrid work schedules and reinforcement of control measures. Conclusion: This study explores the challenges facing employees during the different stages of COVID-19 adaptation and the associated mental health impacts. Gender’s influence on mental health consultations should be considered when planning for public health emergencies, and further research conducted in male dominated industries.